Humic Substances as a Feed Supplement and the Benefits of Produced Chicken Meat - Slavomír Marcinčák; Boris Semjon; Dana Marcinčáková; Anna Reitznerová; Dagmar Mudroňová; Janka Vašková; Jozef Nagy (Life, 2023)
Humic substances with a high proportion of humic acids (more than 40%) have been classified by the European Commission as feed materials that can be used in animal nutrition since 2013. A protective effect on the intestinal mucosa, as well as anti-inflammatory, adsorptive and antimicrobial properties, were recorded. Nutrient absorption, nutritional status and the immune response in chickens supplemented with HSs were significantly improved. HSs have the ability to enhance protein digestion as well as the utilization of calcium and trace elements. They are known to improve feed digestibility as a result of maintaining an optimal pH in the gut, leading to lower levels of nitrogen excretion and less odor in the husbandry environment. HSs not only increase digestibility and result in greater utilization of the feed ration but also improve the overall quality of the meat produced. They increase the protein content and reduce the fat content in breast muscles. They also contribute to improving the sensory characteristics of the meat produced. Their antioxidant properties improve the oxidative stability of meat during storage. The influence of HSs on fatty acid composition may be one of the reasons that meat has a more beneficial effect on the health of consumers.